Avaliação da espessura da camada de fibras nervosas da retina após a trabeculectomia - Nikias Alves da Silva (2012)
OBJECTIVES: To analyze retinal nerve fiber layer thickness (RNFL) before and after trabeculectomy with optical coherence tomography (Stratus OCT 3), and correlate the possible changes with intraocular pressure (IOP) reduction. MATERIAL AND METHODS: 47 eyes of 39 patients with primary open-angle glaucoma were submitted to an optical coherence tomography exam (Stratus OCT 3) 1 week before and 3 months after trabeculectomy. Patients were divided in two groups according with visual field loss: early and moderate glaucoma (MD between -0.7dB and 9.5dB), and advanced glaucoma (MD above 9.5dB), in a way that 21 eyes of 17 patients had early and moderate glaucoma and 26 eyes of 22 patients, advanced glaucoma. IOP was also measured 1 week before and 3 months after surgery. RESULTS: Mean IOP decreased from 25.24 ± 9.27 mmHg with maximum tolerated ocular hypotensive medication before the trabeculectomy to 11.29 ± 4.68 mmHg with no medication, 3 months after the surgery (reduction of 44.73%, P<0.01) in eyes with early and moderate glaucoma, and 19.46 ± 3.85 mmHg to 9.73 ± 2.66 mmHg (reduction of 50.0%, P<0.01) in eyes with advanced glaucoma. There was no significant change in the mean overall RNFL thickness after trabeculectomy in both groups (early and moderate glaucoma: -3.09 ± 6.81 m, P=0.051; advanced glaucoma: 1.82 ± 5.14 m, P=0.083). However, quadrant analysis showed a significant decrease in RNFL thickness in the superior and nasal quadrants in early and moderate glaucoma group (superior: -6.19 ± 12.50 m, P=0.034; nasal: -7.52 ± 13.95 m, P=0.023), and a significant increase in the temporal quadrant in advanced glaucoma group (3.92 ± 8.45 m, P=0.026). CONCLUSIONS: There was no significant change in the mean overall RNFL thickness in both groups after IOP reduction. In the quadrant analysis, a significant decrease in the RNFL thickness was observed in the superior and nasal quadrants in the early and moderate glaucoma group, and a significant increase in the temporal quadrant in the advanced glaucoma group.